Iron Oxide Nanoradiomaterials: Combining Nanoscale Properties with Radioisotopes for Enhanced Molecular Imaging - Pellico, Juan; Llop, Jordi; Fernández-Barahona, Irene; Bhavesh, Riju; Ruiz-Cabello, Jesús; Herranz, Fernando (Contrast Media & Molecular Imaging, 2017)
The combination of the size-dependent properties of nanomaterials with radioisotopes is emerging as a novel tool for molecular imaging. There are numerous examples already showing how the controlled synthesis of nanoparticles and the incorporation of a radioisotope in the nanostructure offer new features beyond the simple addition of different components. Among the different nanomaterials, iron oxide-based nanoparticles are the most used in imaging because of their versatility. In this review, we will study the different radioisotopes for biomedical imaging, how to incorporate them within the nanoparticles, and what applications they can be used for. Our focus is directed towards what is new in this field, what the nanoparticles can offer to the field of nuclear imaging, and the radioisotopes hybridized with nanomaterials for use in molecular imaging.